2012
DOI: 10.1016/j.jembe.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of Calcidiscus leptoporus under nitrogen and phosphorus limitation

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. The coccolithophore Calcidiscus leptoporus was grown in batch culture under nitrogen (N) as well as phosphorus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 23 publications
6
59
0
Order By: Relevance
“…Mean exponential growth rates for C. braarudii at 15 • C were 0.68 d −1 . These values are well within the ranges reported in other studies carried out at similar temperatures for Calcidiscus (Langer et al, 2006;Buitenhuis et al, 2008;Fiorini et al, 2010Fiorini et al, , 2011Langer et al, 2012;Candelier et al, 2013;Müller et al, 2014) and H. carteri (Stoll et al, 2002;. Exponential growth rates of 0.4-0.5 d −1 signify that roughly half of the culture population undergoes cell division each day.…”
Section: Growth Ratessupporting
confidence: 89%
“…Mean exponential growth rates for C. braarudii at 15 • C were 0.68 d −1 . These values are well within the ranges reported in other studies carried out at similar temperatures for Calcidiscus (Langer et al, 2006;Buitenhuis et al, 2008;Fiorini et al, 2010Fiorini et al, , 2011Langer et al, 2012;Candelier et al, 2013;Müller et al, 2014) and H. carteri (Stoll et al, 2002;. Exponential growth rates of 0.4-0.5 d −1 signify that roughly half of the culture population undergoes cell division each day.…”
Section: Growth Ratessupporting
confidence: 89%
“…A widely held, but by no means uncontested (Langer et al, 2012;Langer et al, 2013b), notion is that nutrient limitation leads to increased calcification rate, which in turn leads to a higher overall cell density and thus increased sinking rate (Baumann et al, 1978). Indeed, several studies have shown an increase in E. huxleyi's PIC / POC ratio due to nutrient limitation regardless of the calcification rate (Paasche, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These measures ensure robust, unbiased results (Langer et al 2006;Langer and Benner 2009;Langer and Bode 2011;Langer et al 2012). Recently, it was shown that results based on an objective, biometrical malformation index compare well with the classical, subjective categorization (Bach et al 2012).…”
Section: Methodsmentioning
confidence: 99%